Analyzing the dihedral scattering component of P-band SAR signals for trunk permittivity estimation – a concept study - Anke Fluhrer; Hamed Alemohammad; Thomas Jagdhuber (Science of Remote Sensing)
A new retrieval method, based on a hybrid decomposition technique and the extended (x-) Fresnel model, is proposed for estimating trunk permittivity from polarimetric P-band SAR observations. P-band SAR observations of NASA's Airborne Microwave Observatory of Subcanopy and Subsurface (AirMOSS) mission campaign are employed to test the proposed retrieval method at individual measuring stations across the U.S. between 2013 and 2015. In order to test the feasibility of the x-Fresnel model for such analyses and its sensitivity to required input parameters, a detailed sensitivity study revealed that at P-band frequencies there is a need to account for scattering losses, phase differences, as well as potential depolarization effects due to surface roughness. The decomposed dihedral scattering component increases with increasing vegetation cover from barren land at one station (control station) to homogeneously forested stations (target stations). Overall, no clear correlation between the amount of dihedral scattering and estimated trunk permittivity could be found, which is expected due to the architecture of the employed method. With the proposed approach, the estimated trunk permittivity varies between 2.4 and 59.7 [-], where the barren land and less dense forested stations show lower trunk permittivity. At these stations, the dihedral scattering is not the dominant scattering mechanism within the total SAR signal, which violates the physics of the proposed approach. At stations with dominant dihedral scattering, reasonable correlations (with r ranging from ±0.1 to ±0.64) between estimated trunk permittivity and AMSR2 relative water content (RWC), MODIS evapotranspiration (ET), in-situ measured relative humidity (RH), and air temperature (Tair) could be found. These parameters are used for analyzing the feasibility of the proposed approach as no in-situ trunk moisture measurements are available for the investigated stations and years. Hence, P-band SAR observations that exhibit sufficiently high dihedral scattering portions can be used for estimating trunk permittivity and extend the potential applications of remote sensing for climate research.